2018
DOI: 10.1007/s11748-018-0922-1
|View full text |Cite
|
Sign up to set email alerts
|

Atraumatic tension hemothorax associated with ruptured aneurysm of intercostal artery–azygous fistula: a case report

Abstract: Atraumatic tension hemothorax is extremely rare. We report a case of 62-year-old woman presented with obstructive and hypovolemic shock status by tension hemothorax due to ruptured aneurysm of congenital intercostal artery-azygous fistula. Contrast-enhanced computed tomography and aortography revealed an aberrant 12th intercostal artery flowing into the aneurysm with a fistula draining into the azygous vein and the rupture of aneurysm. Our experience indicates that the rupture of congenital arteriovenous fistu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…To date, only one study reported a case of a patient with IAA caused by an AVF. 7 In our patient, AVF was considered to be the cause of IAA, but the cause of AVF development remained unknown. Aneurysm formation and inflow arterial dilation (size, 6 mm) were observed secondary to high flow associated with AVF.…”
Section: Discussionmentioning
confidence: 81%
“…To date, only one study reported a case of a patient with IAA caused by an AVF. 7 In our patient, AVF was considered to be the cause of IAA, but the cause of AVF development remained unknown. Aneurysm formation and inflow arterial dilation (size, 6 mm) were observed secondary to high flow associated with AVF.…”
Section: Discussionmentioning
confidence: 81%
“…A unique aspect of our case is the presence of hemothorax associated with SA-PAF. A literature search for fistula-related hemothorax usually described arteriovenous fistulae in the pulmonary circulation and previous papers discussing SA-PAFs do not appear to mention hemothorax as a complication [ [6] , [7] , [8] ]. Given its presence and the significant reduction in chest tube fluid volume after embolization, it is reasonable to deduce that the SA-PAF was the source of bleeding into the pleural space.…”
Section: Discussionmentioning
confidence: 99%
“…Tension hemothorax is a well-known complication of trauma and thoracic aortic aneurysm rupture [[1], [2], [3], [4]], while central venous line placement usually causes massive hemothorax [5]. In this case the complication of central venous catheter placement caused a subclavian artery laceration and a pleural lesion that led to a far rarer complication such as tension hemothorax, which is the cause of a hypovolemic and obstructive shock at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…Tension hemothorax is a rare event, due to different causes: trauma with fracture of the first rib [1,2], ruptured thoracic aorta aneurysms [3,4], or as a complication of central venous line placement due to inadvertent artery puncture or cannulation [5]. Tension hemothorax leads to both hypovolemic and obstructive shock and request emergency management.…”
Section: Introductionmentioning
confidence: 99%